Effect of surface roughness on sensitivity of unclad fiber-optic sensors - Azrad, Mohamad Hashim; Mohd Rashidi, Salim; Hummad Habib, Qazi; Muhammad Yusof, Mohd Noor; Asrul Izam, Azmi; Mohd Haniff, Ibrahim; Hadi, Manap (Institute of Physics, 2023)
This work presents the effect of surface roughness's effect on transmission characteristics and the sensitivity of unclad fiber optic sensor (FOS). A total of three samples with different surface roughness were fabricated using the chemical etching technique using different chemical solutions which are 49% hydrofluoric acid (HF), 5:1 Buffered Oxide Etchants (BOE), and 7:1 BOE to analyze the spectrum behavior and the performance of these samples. All samples were fabricated by immersing the 4 cm of sensing zone inside the chemical solution according to the etching rate of that solution. Every sample fabricated will be measured using five different concentrations of glucose which were 5g, 10g, 15g, 20g, and 25g as an experiment medium. From the measurement, the results obtained will be analyzed and the graphs were plotted. The power loss for all solutions were analyzed and the least recorded power loss is 32.49 dB exhibited by FOS fabricated in the 49% HF solution while the best sensitivity in terms of power loss is FOS fabricated in the 5:1 BOE solution with the highest sensitivity of 9.526 dB/g at 5g of glucose concentration.